Diagnosis of twisted blade in rotor system - Lim, Meng Hee (2015)
This paper studies the diagnosis of twisted blade in a multi-stages rotor system using vibra-tion analysis. Experimental study was undertaken to simulate twisted blade conditions in a three stages rotor system. The feasibility of vibration analysis as the technique to detect twisted blade was investigated in this study. Vibration signals were analyzed with both Fou-rier and Wavelet transforms for comparison purposes. Experimental results show that twisted blade can be detected by comparing the pattern in both the vibration spectrum and wavelet scalogram. The feasibility and effectiveness of wavelet analysis as compared to vibration spectrum to detect twisted blade was also discussed and presented in this paper.